2014
DOI: 10.1117/12.2066400
|View full text |Cite
|
Sign up to set email alerts
|

Chemical depth profiling of photovoltaic backsheets after accelerated laboratory weathering

Abstract: Polymeric multilayer backsheets provide protection for the backside of photovoltaic (PV) module from the damage of moisture and ultraviolet (UV). Due to the nature of multilayer films, certain material property characterization of a backsheet could only be studied by examining its cross-section parallel to the thickness direction of the film. In this study, commercial PPE (polyethylene terephthalate (PET)/PET/ethylene vinyl acetate (EVA)) backsheet films were aged on the NIST (National Institute of Standards a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…[41,42] It is also possible to observe in 1730 cm -1 the stretching of the C=O bonds of the esters and the stretching of the CH bonds of the methyl groups external to the ring, in 2975 cm -1 . [41][42][43] It is observed that the addition of Ag-based antimicrobials do not cause significant changes in the polycotton structure at short-range. As a complementary analysis to micro Raman spectroscopy, FTIR measurements were performed to investigate the functional groups of products after the incorporation of the two Ag-based antimicrobial solutions into the polycotton ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…[41,42] It is also possible to observe in 1730 cm -1 the stretching of the C=O bonds of the esters and the stretching of the CH bonds of the methyl groups external to the ring, in 2975 cm -1 . [41][42][43] It is observed that the addition of Ag-based antimicrobials do not cause significant changes in the polycotton structure at short-range. As a complementary analysis to micro Raman spectroscopy, FTIR measurements were performed to investigate the functional groups of products after the incorporation of the two Ag-based antimicrobial solutions into the polycotton ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The 1316 cm −1 band corresponds to C-CH and O-CH bending. PET back-sheets have main characteristics bands at 1144 cm −1 , 1031 cm −1 , and 978 cm −1 due to mixed-mode (glycol C-O stretch + ring CH in-plane bend), mixed-mode (ring CH in-plane bend + COC + glycol C-O stretch, C-C stretch +CCO bending), and mixed-mode (O-CH2 stretch + glycol C-C stretch +ring torsion), respectively [28]. The Raman spectra show no significant difference in the extracted back-sheet compared to the reference PET back-sheet, which is also confirmed by FTIR.…”
Section: Resultsmentioning
confidence: 99%
“…The Raman spectra of the PET substrate before and after 500h at 120°C are presented in Figure 7. The initial spectrum exhibits the conventional vibration bands of PET [26,27]. There was no spectral modification after thermal ageing.…”
Section: Pet Substrate Ageingmentioning
confidence: 93%